An innovative public-private partnership: New approach to development - SAMII, Ramina (Institutional Knowledge at Singapore Management University, 2002)
This paper is focused on the development of new services by nonprofit organizations for groups of companies within a particular sector in industry. It is based oil a case study of ail actual implementation by United Nations Industrial Development Organization (UNIDO) in collaboration with a number of other organizations to upgrade the capabilities of automotive component suppliers in India, to enable them to supply to world-class Manufacturers. We draw upon the traditional literature available on new product and service development for firms introducing new products and services for maximizing profit, and contrast those approaches with the approach adopted by nonprofit organizations. We also carry Out a comparative analysis between UNIDO's partnership model and the traditional model to highlight the innovation aspects and advantages of the former from the developmental perspective. Ail attempt is also made to illustrate the pre-formation. formation and post-formation challenges faced by the new cooperation model that envisages the participation of public and private partners.